Morphological variation of aplectana hylambatis (Nematoda: Cosmocercidae) from different anuran hosts and localities in Argentina - Gonzalez, Cynthya Elizabeth (2019)
Aplectana hylambatis is a nematode witha wide geographic distribution and low host specificity. In spite of numerousreports, until this moment, the morphological variations between differenthosts and localities have not been studied. We studied 401 specimens collectedfrom five host species from seven localities in Argentina, and examined thefollowing morphological characters: mamelon-like cuticular protuberancesanterior to the vulva, structure of the gubernaculum and the spicules, numberand arrangement of caudal papillae, and the measurements of twelve charactersin females and eleven characters in males. The results showed that mamelon-likeprotuberances and caudal papillae varied in number and arrangement between differenthosts and localities. The metrical study revealed that five characters in malesand six in females contributed to variability; nine characters showedsignificant differences between host species and localities. Specimens of A.hylambatis collected from R. arenarum formed a group clearly differentiatedfrom the rest of the specimens. The results from this study highlight theimportance of examining as many specimens as possible from different hostsamples and from several localities to cover the intraspecific variations.